Pelayanan Permasalahan Dan Penempatan Tenaga Kerja Pada Dinas Tenaga Kerja (Disnaker) Kota Medan - Harahap, Tawarni Roha; M. Nawawi, Zuhrinal (Lembaga Riset Ilmiah, 2022)
The problem of employment is a dilemma that has a high complexity, but it demands to be addressed immediately because if it is not addressed it will increase the number of unemployed, while the future trend of growth in employment opportunities is relatively small, this will lead to a larger gap between job seekers and opportunities. available, will then have implications in various aspects of people's lives such as decreasing purchasing power, and increasing the number of poor people. The consequences will continue in the ability of education, health, and people's welfare. This study aims to find out the efforts or policies of the Medan City Manpower Service to provide employment placement services to 2 parties, namely job seekers and companies providing job opportunities, not only that the role of the Medan City Manpower Office can mediate disputes between workers and companies due to concurrency of work energy experiencing Termination of Employment (PHK) and prizes. Rights and employment guarantees. This research was conducted through interview guidelines with narrative research, the author directly observed the field. The availability of a skilled workforce and education is one of the formal conditions for company field providers, of course, the Medan City Manpower Office must be able to prepare skills training for job candidates. Provision of information technology where job market services using an online system are not yet available so that the process of registering job seekers, making yellow cards, registering job vacancies, and presenting job market issues still uses a manual system